2016
DOI: 10.1017/s0032247416000243
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons in snow particulates around Longyearbyen and Barentsburg settlements, Spitsbergen

Abstract: Contamination of snow cover has been investigated in the Longyearbyen (78°13 N, 15°38 E) and Barentsburg (78°3 N, 14°12 E) areas, which are situated in the southwest part of Spitsbergen (Svalbard archipelago). Snow cover was sampled in two winter seasons, 2012–2013 and 2013–2014, at 54 locations within potentially contaminated areas. Sampling incorporated the whole snow mass and was combined with morphological observations as well as thickness and density measurements. Meltwater and suspended solids were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…In Himalayan, Tibetan and Xinjiang sites 15,[35][36][37] , as well as in Japanese snow 50 B(b)F and B(k)F concentrations consistently remain higher than B(a)P. European snow samples usually also show the same prevalence of B(b)F and B(k)F 17,[38][39][40][41]43 . In Arctic sites this predominance is generally less pronounced: the three isomers exist at similar levels in Svalbard snow 8,51 , while B(a)P prevailed in northwestern Canadian locations and far east Russian background sites 46,52 . In Antarctica, a clear B(a)P predominance exists in Northern Victoria Land 53 and in the Talos Dome ice core 13 .…”
Section: Discussionmentioning
confidence: 97%
“…In Himalayan, Tibetan and Xinjiang sites 15,[35][36][37] , as well as in Japanese snow 50 B(b)F and B(k)F concentrations consistently remain higher than B(a)P. European snow samples usually also show the same prevalence of B(b)F and B(k)F 17,[38][39][40][41]43 . In Arctic sites this predominance is generally less pronounced: the three isomers exist at similar levels in Svalbard snow 8,51 , while B(a)P prevailed in northwestern Canadian locations and far east Russian background sites 46,52 . In Antarctica, a clear B(a)P predominance exists in Northern Victoria Land 53 and in the Talos Dome ice core 13 .…”
Section: Discussionmentioning
confidence: 97%
“…Svalbard is a remote archipelago, yet it is exposed to long-range transported contamination. While the exposure to external factors has been known for a long time (e.g., [1,2]), the local pollution there may be more important in some locations, such as settlements [3,4] which were typically established as mining towns. The mining, power production, transport, waste and sewage disposal all contribute to the local pollution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Polkowska et al (2011) also reported that pollutants from the Europe could be transported to Svalbard through longrange transport. In addition, it is noteworthy that there exist many regional pollution sources, including local residents (Andersen et al 2004), e reconstructed photosynthetic biomass variations based on phytol in Ny-Ålesund (Yang et al 2019), f loadings for factor 1 (PC1) represents the total organic matter input in the palaeo-notch sediment (Yang et al 2019) activities (Kallenborn et al 2017), scientific expedition (Jia et al 2012), mining activities (Abramova et al 2016) and tourist shipping (Kozak et al 2013). The pollution could be recorded in the lacustrine sediments (Jiang et al 2011a;Liu et al 2012), ice cores (Isaksson et al 2003) and even seal hairs (Sun et al 2006b).…”
Section: Environmental Pollution and Anthropogenic Activitiesmentioning
confidence: 99%